Between worlds and thresholds: death, the (un)knowable, and reassembling the social - Sabry, Aya Walyeldin Shafik Osman (AUC Knowledge Fountain, 2015)
How does death, and the dead, shape the making of living subjectivities? How do the worlds of the dead entwine with the worlds of the living? Do the dead have an agency that engages the spaces of the living and their epistemes? Based on eight-month fieldwork during 2014, this ethnography focuses on a network of villages in Bilbeis in Egypt to analyze the sociality of death and how the social is reassembled to comprise networks among the living and the dead. By studying the everydayness of death through memories of the dead, narratives of the past, casual talks surrounding death, and the spatiality of death in terms of the historical significance of a particular cemetery and the daily lives of its surrounding villages, I trace the power configurations and historical processes that shaped the development of contemporary understandings of death and subjectivity within this self-proclaimed Muslim community. Drawing on Latour’s works on (re)assemblages and networks, my research calls attention to motion in its attempts to trace death, space, and knowledge(s) of death. It questions the conceptualization of death as a self-contained event or finality (an “ending”) and instead, reframes it as a dynamic process that is constitutive of life – a movement that severs certain ties while reconstituting others. Death is then a different form of existence, and the dead are simultaneously present and absent, with (im)material lives of their own, whether in a different metaphysical realm or in the memories, affectivities, and spaces of the living. The entanglements of life and death also extend to the cemetery, which presents a space that is contested and (re)shaped, for it is simultaneously a space of the ordinary – another structure in the everyday landscape – as well as a space of the extraordinary, of otherness, of transgression – where unconventional human activities, such as crime, occur as well as metaphysical beings operate at night. In this sense, there are different imaginaries and networks of subjectivities and agencies, both human and non-human, at work.